2021
DOI: 10.1056/nejmoa2104983
|View full text |Cite|
|
Sign up to set email alerts
|

Preliminary Findings of mRNA Covid-19 Vaccine Safety in Pregnant Persons

Abstract: Background Many pregnant persons in the United States are receiving messenger RNA (mRNA) coronavirus disease 2019 (Covid-19) vaccines, but data are limited on their safety in pregnancy. Methods From December 14, 2020, to February 28, 2021, we used data from the “v-safe after vaccination health checker” surveillance system, the v-safe pregnancy registry, and the Vaccine Adverse Event Reporting System (VAERS) to characterize the initial safety of mRNA Covid-19 vaccines in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

42
598
7
17

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 781 publications
(735 citation statements)
references
References 16 publications
42
598
7
17
Order By: Relevance
“…In a study performed by Shimabukuro et al, who examined 35,691 women v-safe participants 16 to 54 years of age that identified as pregnant, injection site pain was the most frequently reported by pregnant women compared to non-pregnant women. Among 3958 pregnant women enrolled in the v-safe pregnancy registry, 827 had a completed pregnancy, of which 115 (13.9%) experienced pregnancy loss and 712 (86.1%) resulted in a live birth (mostly among participants with vaccination in the third trimester) [ 31 ]. Although no neonatal deaths were reported, adverse neonatal outcomes included preterm birth (in 9.4%) and small size for gestational age (in 3.2%) [ 31 ].…”
Section: The Safety and Efficacy Of Covid-19 Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study performed by Shimabukuro et al, who examined 35,691 women v-safe participants 16 to 54 years of age that identified as pregnant, injection site pain was the most frequently reported by pregnant women compared to non-pregnant women. Among 3958 pregnant women enrolled in the v-safe pregnancy registry, 827 had a completed pregnancy, of which 115 (13.9%) experienced pregnancy loss and 712 (86.1%) resulted in a live birth (mostly among participants with vaccination in the third trimester) [ 31 ]. Although no neonatal deaths were reported, adverse neonatal outcomes included preterm birth (in 9.4%) and small size for gestational age (in 3.2%) [ 31 ].…”
Section: The Safety and Efficacy Of Covid-19 Vaccinesmentioning
confidence: 99%
“…Among 3958 pregnant women enrolled in the v-safe pregnancy registry, 827 had a completed pregnancy, of which 115 (13.9%) experienced pregnancy loss and 712 (86.1%) resulted in a live birth (mostly among participants with vaccination in the third trimester) [ 31 ]. Although no neonatal deaths were reported, adverse neonatal outcomes included preterm birth (in 9.4%) and small size for gestational age (in 3.2%) [ 31 ]. Even more, although not directly comparable, there appeared no significant difference in adverse events and neonatal outcomes compared to other studies with similar cohorts before the COVID-19 pandemic.…”
Section: The Safety and Efficacy Of Covid-19 Vaccinesmentioning
confidence: 99%
“…Somit sind künftig Daten zum Outcome dieser Schwangerschaften zu erwarten [3]. Eine jüngst publizierte Registerstudie (V-Safe) zu vorläufigen Ergebnissen bei über 30.000 trotz Schwangerschaft geimpften Frauen zeigte, dass impfbedingte Nebenwirkungen sich bis auf vermehrte lokale Schmerzen im Bereich der Impfung nicht von denen der Nichtschwangeren unterschieden [4]. Häufigkeit und Art von unerwünschten Schwangerschafts-und Neugeborenenereignissen waren vergleichbar mit den vorbekannten Inzidenzen vor der COVID-19-Pandemie [4] [6].…”
Section: Schutz Durch Impfen Gegen Sars-cov-2unclassified
“…A large study by Shimabukuro et al recently described no glaring concerns except spontaneous abortions in pregnant women who got the mRNA vaccine [ 7 ]. It was proposed that antibodies against SARS-Cov2 spike protein might cross-react with human placental protein syncytin 1, causing damage to placenta, but no similarity was noticed in amino acid sequence of both proteins.…”
mentioning
confidence: 99%